Parenting Information on Social Media: Systematic Literature Review - Ellen Mertens; Guoquan Ye; Emma Beuckels; Liselot Hudders (JMIR Publications, 2024)
BackgroundSocial media has become extremely popular among parents to seek parenting information. Despite the increasing academic attention to the topic, studies are scattered across various disciplines. Therefore, this study broadens the scope of the existing reviews by transcending narrow academic subdomains and including all relevant research insights related to parents' information seeking on social media and its consequent effects. ObjectiveThe aims of this systematic literature review were to (1) identify influential journals and scholars in the field; (2) examine the thematic evolution of research on parenting and social media; and (3) pinpoint research gaps, providing recommendations for future exploration. MethodsOn the basis of a criteria for identifying scholarly publications, we selected 338 studies for this systematic literature review. We adopted a bibliometric analysis combined with a content thematic analysis to obtain data-driven insights with a profound understanding of the predominant themes in the realm of parenting and social media. ResultsThe analysis revealed a significant increase in research on parenting and social media since 2015, especially in the medical domain. The studies in our review spanned 232 different research fields, and the most prolific journal was JMIR Pediatrics and Parenting. The thematic analysis identified 4 emerging research themes in the studies: parenting motivations to seek information, nature of parenting content on social media, impact of parenting content, and interventions for parents on social media. ConclusionsThis study provides critical insights into the current research landscape of parenting and social media. The identified themes, research gaps, and future research recommendations provide a foundation for future studies, guiding researchers toward valuable areas for exploration.